THE EFFECT OF CELEBRITY ENDORSEMENT CREDIBILITY ON PURCHASE INTENTION IN PREMIUM PRICE FOOD - Hafifah Rahmanisah; Jul Aidil Fadli (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2022)
The purpose of the study was to examine the dimensions that build celebrity endorsement credibility, as well as the impact of celebrity endorsement credibility on purchase intention and willingness to buy at a premium price on food products.  The survey was conducted on 125 respondents, then Structural Equation Model Partial Least Square analysis was employed to determine the level of significance and the relationship between variables. The result shows that the trustworthiness, expertise, and attractiveness of the endorser can form celebrities’ credibility. Furthermore, the credibility of celebrity endorsements can increase purchase intention and consumers' willingness to buy at a premium price. This research can guide celebrities, especially in the context of social media, to promote their endorsed products.